Analisis Perbandingan Decision Tree dan Random Forest Untuk Prediksi Penyakit Berdasarkan Gejala Pasien - Sunarto Taliki; Serwin Serwin; Haditsah Annur; Mohamad Rayhan A Ismail (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2026)
Basic principles of public health form a crucial foundation in efforts to protect and improve public health, with a primary focus on disease prevention. In the era of transformation, a science capable of prediction is needed, such as the use of decision tree and random forest algorithms, which have the ability to generate accurate predictions through data processing by forming decision trees. This research utilizes a public dataset on